2019
DOI: 10.1111/ejh.13294
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stem cell transplantation for myelofibrosis patients aged ≥65 years

Abstract: Introduction Myelofibrosis (MF) is a disease of elderly with median age of 65 years at diagnosis. Allogeneic stem cell transplantation (ASCT) currently is the only potentially curative option, although associated with treatment‐related morbidity and mortality. Development of reduced intensity conditioning (RIC) regimens enabled transplant to be performed successfully in older patients. Objectives and Methods To evaluate outcome of transplantation among elderly patients (≥65 years), we conducted retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…Over the last couple of decades use of reduced‐intensity conditioning (RIC) has improved access to patients to this life‐saving and curative procedure. Kroger et al reported in patients with a median age of 67 years (65–74 years) outcome was comparable to other reports with 6 years estimated progression‐free survival and OS of 60% and 64%; one‐year NRM was 21% 8 . This study predominantly included fludarabine and busulfan (FB) RIC.…”
Section: Eligibility Of Allogeneic Stem Cell Transplantationsupporting
confidence: 79%
See 1 more Smart Citation
“…Over the last couple of decades use of reduced‐intensity conditioning (RIC) has improved access to patients to this life‐saving and curative procedure. Kroger et al reported in patients with a median age of 67 years (65–74 years) outcome was comparable to other reports with 6 years estimated progression‐free survival and OS of 60% and 64%; one‐year NRM was 21% 8 . This study predominantly included fludarabine and busulfan (FB) RIC.…”
Section: Eligibility Of Allogeneic Stem Cell Transplantationsupporting
confidence: 79%
“…Kroger et al reported in patients with a median age of 67 years (65–74 years) outcome was comparable to other reports with 6 years estimated progression‐free survival and OS of 60% and 64%; one‐year NRM was 21%. 8 This study predominantly included fludarabine and busulfan (FB) RIC. Another study using melphalan based conditioning regimen in patients > 70, included 53 patients with any diagnosis including six MF patients: after 31 months follow up 2‐year OS, PFS, NRM was respectively 69%, 64%, and 17%.…”
Section: Eligibility Of Allogeneic Stem Cell Transplantationmentioning
confidence: 99%
“…3,4 There is an increasing use of allo-HCT in older patients with hematological malignancies, which has yielded reasonable results. 5,6 Regarding MF, two small retrospective series from academic centers 7,8 have shown favorable allo-HCT outcomes in elderly MF patients, particularly in those with minor comorbidities. 8 These studies have demonstrated the feasibility of the procedure in selected older adults with MF, but a comparison of allo-HCT results with nontransplant approaches is lacking in this age group.…”
Section: Introductionmentioning
confidence: 99%
“…These results may caution the application of higher-intensity treatment in such a vulnerable population with severe disease burden and frailty, irrespective of age. 37,38 We acknowledge several limitations, which are mainly due to the retrospective nature of our study. We cannot fully exclude the selection bias of patients receiving splenic irradiation.…”
Section: Discussionmentioning
confidence: 99%